Langerhans cell histiocytosis: 23 years' paediatric experience highlights severe long-term sequelae. Issue 3 (August 2014) - Martin, Allison; Macmillan, Susan; Murphy, Dermot; Carachi, Robert
Purpose: To review the presentation and outcome of patients with Langerhans cell histiocytosis attending The Royal Hospital for Sick Children, Glasgow over a 23-year period. Method: Thirty-one children were diagnosed with Langerhans cell histiocytosis between January 1990 and December 2012. Retrospective information from medical records was gathered on age at diagnosis, presenting symptoms, classification of disease, treatment and long-term outcome. Results: There were 17 boys and 14 girls; median age at diagnosis 2 years 9 months (interquartile range: 1 year 6 months to 4 years 4 months). Eleven were below 2 years and two were below 6 months of age at diagnosis. Eighteen (58%) children had single system disease of which four were multifocal; 13 (42%) had multisystem disease. Seventeen children improved with conservative treatment. Fourteen required steroids and dual agent chemotherapy; three required further chemotherapy. One child died. Two children had successfully treated relapses. Ten developed diabetes insipidus, seven were growth hormone deficient, two suffered from hypothyroidism and one panhypopituitarism. Median follow-up of the cohort was 8 years 10 months (interquartile range: 5 years 5 months to 12 years 7 months). Conclusion: Langerhans cell histiocytosis is a rare disease in infants and young children, with a variable course ranging from self-limiting to life threatening. In very young children (under 2 years of age), multisystem disease is more common, requiring intensive chemotherapy and lifelong follow-up. Lasting sequelae were identified in over a third of patients, including endocrine dysfunction, hearing difficulties, neurological and psychological problems.